Maize research at IAR Samaru - Ado, S.; Showemimo, F.; Alabi, S.; Badu-Apraku, Baffour; Menkir, A.; Usman, I.; Abdullahi, U.S. (2007)
Maize (Zea mays L) research at the Institute for Agricultural Research (IAR), Samaru was initiated in the 1950s with the goal of developing adapted high yielding varieties and hybrids. Germplasm materials were collected from local sources as well as from different countries, including Columbia, Kenya, Mexico and the US' By the 1960s. IAR Samaru was actively participating in the National cooperative Trials, the West African Maize Variety Trials of the OAU-STRC Joint Project as well as the East African Maize Variety Trial coordinated by the East African Agricultural and Forestry Research organization (EAAFRO). Kitale, Kenya. By 197 6,a total of nine new open- pollinated varieties had been developed and released to farmers' The new maize technology packages developed gave up to 98% higher grain yield than the farmers traditional methods of production. In the 1990s, collaborative research continued under the west and Central African Collaborative Maize Research Network (WECAMAN) and the sasakawa Global20006G-2000) which, in partnership with IAR, disseminated new maize technologies to Nigerian farmers. In 2001, three new varieties developed and tested in collaboration With IITA-WECAMAN were registered and released to Nigerian farmers. Recently, Quality Protein Maize (QPM) trials were initiated in collaboration with lITA-WECAMAN.SG-2000, and CIMMYT and promising results have been obtained. The Institute continues to collaborate with national and international research organizations in maize improvement. The five decades of collaborative maize research at Samaru have contributed to increased land area under maize, increased grain yield, and increased income to maize farmer.